Structure-property relationship of photo-curable resins for 3D printing (2020)
ABSTRACT: In this academic work the creation of a structure-property relationship of a photo-curable resin from Aycubic Company was sought. To achieve this, test specimens were design and printed with the Vat photopolymerization Additive Manufacturing technique, most widely known as 3D-printing of photo-curable resins. For the printing process of the test specimens a LCD printer was used. The PHOTON machine by Anycubic was advertised as a SLA apparatus (Stereolithography) and was available at the CCComposites 3D-printing laboratory. I managed to find out the optimum printing parameters and the influence of such parameters in the final mechanical properties of the final part. Not only were these parameters studied but also the post curing process. Traction tests were performed to acquire the strain and stress of the material. By using statistical analysis and a Weibull distribution, the Weibull module regarding both strength data and strain data was obtained as well as the Strength vs strain curve. Moreover, the maximum effective resolution of the printer was determined by means of the design and printing of several micro structures in order to verify the feasibility of this technology for the creation of polymer matrix nanocomposites, and the possible insertion of carbon nanotubes (CNT’s) and Copper nanoparticles (CNP’s).